PENDIDIKAN SUSILA SEBAGAI UPAYA MENCEGAH KENAKALAN REMAJA - I Ketut Sudarsana (Guna Widya: Jurnal Pendidikan Hindu, 2018)
Juvenile delinquency occurs because of failure to undergo psychological development processes, both as a teenager and still in childhood. The childhood and teenage years are actually experienced so briefly, so sometimes between physical, psychological, and emotion does not develop simultaneously. Psycho- logically, juvenile delinquency is a manifestation of unresolved conflicts well in childhood as well as adolescent perpetrators. Teenagers sometimes experience psychological distress in their past which is the result of rough and unpleasant treatment of the environment. In addition, there is also psychological pressure on the condition of the environment, especially regarding the economy that makes him feel inferior. Susila education that takes place in schools is expected to be able to form the spiritual behavior of adolescents according to the teach- ings of Hinduism, as well as away from any behavior that leads to juvenile delin- quency.